Translanguaging for Equal Opportunities Speaking Romani at School - Heltai, János Imre; Tarsoly, Eszter (Contributions to the Sociology of Language [CSL], 2023)
This multi-authored monograph offers a state-of-the-art analysis of how translanguaging supports bilingual Roma students' learning in monolingual school systems. Co-written by academic and non-academic participants, it is an essential reading for researchers, pre- and in-service teachers of Romani-speaking students and experts working with students whose home languages are different from the teachers' and the school curricula.